An Ulam stability result on quasi-b-metric-like spaces - Alsulami Hamed H.; Gülyaz Selma; Karapınar Erdal; Erhan İnci M. (Open Mathematics, 2016)
In this paper a class of general type α-admissible contraction mappings on quasi-b-metric-like spaces are defined. Existence and uniqueness of fixed points for this class of mappings is discussed and the results are applied to Ulam stability problems. Various consequences of the main results are obtained and illustrative examples are presented.